Islamic Financial Institutions as Strengthening The Economy of The Ummah (Study on The Application of Shariah Agreements in Islamic Financial Institutions) - Alif Endy Pamuji; Ach Faqih Supandi; Miftahus Sa’diyah (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2022)
Islamic business institutions (sharia) is one of the instruments used to regulate the rules of Islamic economics. As part of the economic system, it is part of the entire social system. Therefore, its existence must be viewed in the context of the overall existence of society (human), as well as the values that apply in the society concerned. The research method used is a qualitative method with a descriptive approach to analysis. This study uses descriptive analysis research methods. The types of data used are secondary data, data in the form of articles, books and research reports as well as other sources or information relevant to this study. The role of shari'ah financial institutions in encouraging economic growth is to apply the principles of Shari'ah in the management of financial institutions such as buying and selling and profit sharing then indirectly Shari'ah financial institutions not only touch the monetary sector but also have touched the real sector resulting in unstoppable investment flows, resulting in an increase in productive businesses. Which ultimately also increases household income, the state, as well as export-import activities.